135k views
1 vote
Which expression is equal to (−3−i)+(5+6i)? 2+5i7−7−4+11i

User Fmatar
by
4.7k points

1 Answer

1 vote

GIVEN:

We are given the following expression;


(-3-i)+(5+6i)

Required;

Select which of the given expressions is an equivalent.

Step-by-step solution;

We begin by grouping the real parts and the imaginary parts using the principle shown below;


\begin{gathered} (a+bi)+(c+di) \\ \\ =(a+c)+(bi+di) \\ \\ =(a+c)+(b+d)i \end{gathered}

We can now refine as follows;


\begin{gathered} (-3-i)+(5+6i) \\ \\ =(-3+5)+(-i+6i) \\ \\ =(-3+5)+(-1+6)i \\ \\ =2+5i \end{gathered}

ANSWER:

The equivalent expresion is;


2+5i

User Shlomit
by
4.5k points